A new shortcut for competitive sports development? The purpose of and strategy for developing and introducing sepaktakraw in Taiwan - Ding-Yi Wu; Tien-Chin Tan; Yan-Ting Wang (PLoS ONE, 2025)
A growing number of countries and regions have introduced emerging sports in recent years; however, few studies have been conducted to determine how and why they do so. This article focuses on why a new sport, sepaktakraw, was introduced in Taiwan and how strategies for achieving international sporting success were developed in a short period. The sports policy factors leading to the international sporting success model proposed by De Bosscher et al. were adopted as this study’s analytical framework. Data were obtained from official government and sport federation documents, media reports, and semistructured interviews with 18 key stakeholders. This study revealed three main reasons for the introduction of sepaktakraw in Taiwan: (1) low introduction costs, (2) breakthroughs to win medals at the Asian Games, and (3) advantageous entry into international sports organization leadership. Seven aspects are prioritized in Taiwan’s sepaktakraw development strategy: (1) obtaining government financial support; (2) institutionalizing organisational decision-making; (3) taking universities as a breakthrough point and then gradually shifting to promote popularization at the grassroots level; (4) selecting players on the basis of competition results; (5) using school badminton courts; (6) strengthening coach training; and (7) actively participating in and striving to host international tournaments. The findings could provide guidelines and examples for other countries or regions to follow when introducing new sports and moving towards the successful development of competitive sports.